OP0097 DEVELOPMENT OF NEW INTERNATIONAL CLASSIFICATION CRITERIA FOR ANTIPHOSPHOLIPID SYNDROME: PHASE III CASE COLLECTION RESULTS. (2nd June 2020) - Barbhaiya, M.; Erkan, D.; Ahmadzadeh, Y.; Costenbader, K.; Naden, R.; Zuily, S.
Abstract : Background: An international multi-disciplinary effort is underway to develop rigorous, new, consensus- and evidence-based classification criteria for Antiphospholipid Syndrome (APS). The methodological approach includes four phases; we have previously presented phases I and II (item generation and reduction), which resulted in 27 candidate criteria 1 organized in laboratory and clinical domains. Objectives: Phase III (item weighting/threshold identification) is currently underway; here we report initial Phase III case collection results. Methods: We used REDCap, a secure data system, for Phase III international case collection. The candidate criteria of 27 items at the end of Phase II was represented in a standardized case collection form. We asked international physicians interested in APS to provide and rate cases using a Likert scale (+3 to -3: highly likely to highly unlikely to be APS). Cases with higher scores (+2 or +3) were categorized as "highly likely" APS, whereas lower scores (+1 to -3) were categorized as "equivocal or unlikely" APS. Results: We collected 314 potential APS cases (mean age 43.8±14.4 years; 79% female; and 77% white) between 6/2019-8/2019 from 17 sites in Europe (47%), North America (41%), and South America (11%). Majority of cases were potential primary APS (64%); 137 were rated as "highly likely" and 177 as "equivocal or unlikely" APS. Lupus anticoagulant, antiβ2 glycoprotein-I antibody IgG/M, anticardiolipin antibody IgG, arterial thrombosis, venous thromboembolism, microvascular disease, fetal loss between 16-34 weeks, severe preeclampsia, severe placental insufficiency, cardiac valve disease, and low platelet count occurred with higher frequency in the APS cases categorized as "highly likely" (Table). Conclusion: International collection of cases spanning the spectrum of "highly likely" to "equivocal or unlikely" APS provide "real world" assessment of patients being referred for APS evaluation. In next steps, proposed candidate criteria will be further refined, organized, and weighted, and a preliminary threshold for APS classification will be determined. References: [1]Barbhaiya M et al. Phase II Results [abstract]. Arthritis Rheumatol. 2019;71 (suppl 10). Acknowledgments: The project is supported by ACR/EULAR Disclosure of Interests: Medha Barbhaiya: None declared, Doruk Erkan: None declared, Yasaman Ahmadzadeh: None declared, Karen Costenbader Grant/research support from: Merck, GSK, Consultant of: Merck, GSK, Lily, Astra Zeneca, Janssen, Raymond Naden: None declared, Stéphane Zuily: None declared